Enhancing adolescent hypertension prevention in Indonesia through interactive multimedia: Model development and validation - Wijayati, Sugih; Sakundarno, Mateus; Surjoputro, Antono; Budiyono, Budiyono (Narra J, 2024)
Adolescent hypertension is emerging as a significant health challenge. Peer-led interventions utilizing engaging multimedia platforms have demonstrated the potential to enhance prevention behaviors among adolescents. However, there remains a gap in the literature comparing the effectiveness of multimedia intervention with traditional lecture-based approach in adolescent hypertension prevention in Indonesia. The aim of this study was to compare the traditional lecture-based approach and interactive multimedia intervention (e-module, animated videos, and infographics) on adolescents' knowledge, attitudes, and practices regarding adolescent hypertension prevention. A quasi-experimental study with pre-test and post-test control group study was conducted from June to December 2023 in two senior high schools in districts of Pedurungan and Kedungmundu, Semarang, Central Java, Indonesia. To prepare the multimedia model, the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) framework and mapping intervention approach were employed to ensure effective decision-making at each step. A total of 100 high school students were involved, with 50 assigned to the intervention group and 50 to the control group. The intervention group received a multimedia model from the peer educators, while the control group received a traditional PowerPoint-based presentation from the community healthcare workers. The hypertension prevention knowledge, attitude, and practice were assessed using validated questionnaires with 20, 15, and 15 items, respectively. This study found that, after model implementation, significant improvements were observed in students’ knowledge, attitudes, and practices regarding hypertension prevention (all had p<0.001). Specifically, knowledge scores increased by 4.78 points, attitude scores by 10.64 points, and practice scores by 2.9 points. This study highlights that multimedia interventions could significantly improve hypertension prevention behaviors among adolescents by enhancing their knowledge, attitudes, and practices through engaging and interactive multimedia materials.